Caracterización de residuos sólidos domiciliarios generados en la Comunidad Nativa Santo Tomás del distrito de Punchana, Región Loreto, 2022 - Sanchez Lopez, Cassie Yadira (2024)
The objective of this research was to characterize the household solid waste generated in the Santo Tomás Native Community of the Punchana District in 2023. This is a quantitative research with a descriptive-non-experimental approach. Social, economic and environmental information has been obtained from 54 households through a survey; and the methodology of the Guide for the characterization of municipal solid waste of the Ministry of the Environment has been followed. The statistical program SSPS and Excel were used for data analysis. The results show that the per capita generation is 0.774 kg/inhabitant/day, with a projection of 0.189 t/day, 5.67 t/month and 67.99 t/year; being the physical composition of 45.88% inorganic waste (paper, cardboard, glass, plastic, tetra brik, metals, textiles and rubber), 43.89% organic waste (food waste and weed and pruning waste) and 10.23% non-usable waste (single-use plastic bags, sanitary waste, batteries, technopor, inert waste, leftover medicine and wrappers from snacks, cookies, candies, among others); with a density of 704.20 kg/m3. This information is essential for planning various actions regarding the integrated management of solid waste, providing added value to them, generating new employment initiatives and opportunities for the economic development of the population in harmony with the environment.